The Implementation of Classnetwork.net in Teaching and Learning in the University of Brunei Darussalam - Noor, Abdullah Mohd; Sura, Andy Azhar; Hamidon, Zahari (EDUCARE, 2008)
ABSTRACT: Teaching and Learning in Higher Education is an issue for educators in various fields to look into. The rapid growth of online teaching is the mode of instruction increasingly being used by educators today. The present study investigated the implementation of classnetwork.net by undergraduates enrolled in various teacher education programmes. The sample consisted of 102 teacher education students and they were given opportunities to make use of classnetwork.net (an online tool for uploading and downloading lecture notes and teaching materials). The implementation of classnetwork.net as an alternative mode of knowledge delivery to student teachers was made available to students recently. Instead of using traditional lecture method this online mode of delivery is an innovation in University of Brunei Darussalam. A survey method was used to elicited answers to researched questions. This study analyzes online skills (certain aspects) such as numbers of hours using computer and frequency of access the content in classnetwork.net. An effective communication is judged through correlation between online skills and numbers of hours and online skills and frequency of access. The study reports on the effective implementation of this tool as an innovative mode to teaching that will effect learning among students.KEY WORDS: online learning, online learning skills, instructional design, and e-learning.Â Â Â Â About the authors: Assoc. Prof. Dr. Abdullah Mohd Noor, Dr. Andy Azhar Sura, and Dr. Zahari Hamidon are lecturers at the University of Brunei Darussalam. They could be reached at: abdull@shbie.ubd.edu.bn, azhar@shbie.ubd.edu.bn and zham@shbie.ubd.edu.bnHow to cite this article? Noor, Abdullah Mohd, Andy Azhar Sura & Zahari Hamidon. (2008). âThe Implementation of Classnetwork.net in Teaching and Learning in the University of Brunei Darussalamâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.39-52. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 10, 2008); Revised (July 15, 2008); and Published (August 17, 2008).